BURKITT S LYMPHOMA OF THE BREAST AND OVARY, CASE REPORT - Elhaj, Ahmed M.; Mohamadani, A. A.; Sanhouri, Kanan. (Gezira Journal of Health Sciences, 2006)
A 17 year old Sudanese female with breast lump and ovarian mass proved to be    Burkitt s lymphoma of the breast and ovary.  She received 8 cycles of CHOP chemotherapy and Intrathecal methotrexate and achieved complete response. Three years after treatment she is well without recurrence. A lymphoma should always be considered in the differential diagnosis of a breast tumor, especially in very young patients. It needs a different work-up and treatment.